Adams and Jefferson - Peterson, Merrill; Burstein, Andrew (University of Georgia Press, 2023)
Adams and Jefferson: A Revolutionary Dialogue documents the public lives and personal friendship of John Adams and Thomas Jefferson, from their first meeting as delegates to the Second Continental Congress to their deaths on the fiftieth anniversary of the Declaration of Independence. This study takes a look at some of the famous correspondence between the two statesmen who devoted their lives to a new chapter of freedom and self-government. Peterson draws an extended parallel between the backgrounds, experiences, personalities, and intellectual styles of Adams and Jefferson and examines their work in the achievement of independence and the design of new governments for Massachusetts and Virginia. While Adams and Jefferson had much in common, their ideas of human nature, history, society, and government included many differences that would reveal themselves in the course of time. Merrill D. Peterson looks at Adams and Jefferson's relationship across their lives, including their disputes in the midst of the coming French Revolution, their excitement for the establishment of a new American government under the Constitution, their contest for the presidency in 1796, and their eventual reconciliation. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.